PENGEMBANGAN PEMBELAJARAN MATEMATIKA BERBASIS PROBLEM BASED LEARNING TERINTEGRASI WORDWALL UNTUK MENGOPTIMALKAN PEMAHAMAN SISWA KELAS IV PADA MATERI LUAS KELILING PERSEGI - Maitris Yulida; Syafri Ahmad; Salmaini Salmaini (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to develop and implement a mathematics learning model based on Problem Based Learning (PBL) integrated with Wordwall media to optimize students’ conceptual understanding of the area and perimeter of squares at the elementary school level. The research was conducted at SDN 21 Makalo, Kecamatan Sikakap, during the odd semester in response to the low level of students’ conceptual comprehension, where they tended to memorize formulas without understanding their meaning or applying them to real-life contexts. This quasi-experimental research involved two groups: an experimental class taught through PBL integrated with Wordwall and a control class taught through conventional methods. Data were collected using pretest and posttest instruments supported by classroom observations to assess learning activities. The results showed that the experimental class achieved a higher posttest mean score of 82.40 compared to 69.30 in the control class. Furthermore, the N-Gain score of the experimental class reached 0.68, categorized as medium–high, while the control class obtained 0.42, categorized as medium. These findings indicate that integrating PBL with Wordwall effectively enhances students’ engagement, motivation, and conceptual mastery of area and perimeter. The study concludes that this combined approach provides a meaningful learning experience and serves as a relevant and innovative strategy for improving mathematics learning outcomes in elementary schools.